CHALLENGES FOR 21st CENTURY LEARNING IN INDONESIA - . Hendarman (Bandar Lampung University (UBL), 2016)
Corresponding email: and hendarmananwar@gmail.comAbstractTo develop a more advanced and diversified economy and improve its international competitiveness, in education sector, Indonesia focuses the development of 21st century learning skills to the students at all levels to be able to compete with other nations in the world. For this to happen, a number of challenges should be overcome which among others including teachers’ competency, literacy and numeracy skills as measured by PISA, Human Development Index (HDI), and competitiveness index. The engagement of actors or stakeholders within education sector ecosystem plays the pivotal role for the improvement of Indonesia’s education as well as for 21st century learning environment.